Qur’an-Anchored Competency Framework: Thematic Links Between Value Orientations and 21st-Century Skills - Iwan Hermawan; Wahidin Wahidin; Radyallah Agnia Hermawan (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study synthesizes how Qur’anic value orientations tafakkur (Meditation), taʿāwun (collaboration), ḥikmah (wisdom), and iḥsān (excellence/creativity) map onto 21st-century competencies (4C/6C) and articulates a coherent integration framework for Islamic education. Methodology: Adopting a library research design, documents were selected through explicit inclusion–exclusion criteria from databases (e.g., Google Scholar, national portals) and backward reference screening. Eligible sources included scholarly books, peer-reviewed articles, theses/dissertations, regulations, yearbooks, and reputable encyclopedias (print/digital). Data were extracted using a structured matrix and analyzed using qualitative content analysis (NVivo/ATLAS.ti optional). “Measurement” was operationalized as code presence, salience, and co-occurrence patterns across texts. Trustworthiness was supported by expert review of the codebook, intercoder agreement targets (Cohen’s κ ≥ .70), triangulation, and an audit trail. Main Findings: The study identifies strong links between Qur’anic values tafakkur, taʿāwun, ḥikmah, and iḥsān and core 21st-century competencies such as critical thinking, communication, collaboration, and creativity. These connections form a practical Value–Skill–Outcome framework that translates spiritual principles into measurable educational skills, offering a balanced integration of ethical values and modern learning outcomes in Islamic education.. Novelty/Originality of this study: The study moves beyond descriptive parallels by offering a concise, Qur’an-anchored framework that integrates classical values with contemporary competency models for Islamic higher education.